PERUBAHAN UNDANG-UNDANG NOMOR 22 TAHUN 2019 (TENTANG SISTEM BUDIDAYA PERTANIAN BERKELANJUTAN) OLEH UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA DAN PREDIKSI IMPLIKASINYA - Ida Bagus Radendra Suastama; Ida Ayu Komang Juniasih (Forum Manajemen STIMI Handayani Denpasar, 2022)
This study aims to find out which provisions in Law Number 22 of 2019 concerning Agricultural Cultivation Systems were amended by the "Job Creation Law" (Law Number 11 of 2020). This research also aims to find out and understand the rationale and intent underlying the changes made by the Job Creation Law to Law Number 22 of 2019 concerning the Agricultural Cultivation System (hereinafter simply referred to as the Agricultural Cultivation System Law). This research further attempts to estimate predictions related to the implications of these changes by understanding the contents of the new provisions and comparing them with the contents of the amended provisions. This research data collection method is a research method / literature study, especially on primary legal materials, namely laws and regulations. The type of approach and analysis method used in this research is a qualitative approach. The definition of research with a qualitative approach is research that focuses attention on the ideas or values that underlie an act or action of the actor or an event that is related or arises or which is a consequence or result / product of the act / action. The conclusions of this study are: 1. The articles of Law Number 22 of 2019 concerning the Sustainable Agricultural Cultivation System as amended through the Job Creation Act (especially Article 31 of the Job Creation Law) are: Article 19, Article 22, Article 32, Article 43, Article 86, Article 102, and Article 108 of the Law on Sustainable Agricultural Cultivation Systems (Law Number 22 of 2019), as well as the abolition of Article 111 of Law Number 22 of 1999 concerning Sustainable Agricultural Cultivation Systems. 2. The rationale for the amendment of several laws, judging from the comparison between the old provisions and the new provisions of the amended article (comparison between the sound of the articles before and after the amendment), is the idea of providing a legal basis for the Central Government and/or Regional Governments to adopt certain policies or take certain actions related to Agriculture in order to increase Indonesia's attractiveness for investment, business and industry. 3. Things that are expected to occur after the enactment of the Job Creation Act which changes quite a number of laws to increase the attractiveness of Indonesia's investment, is the higher investor confidence and the sense of security of investors to invest in Indonesia, which in turn is expected to increase as well. the value and volume of investment from investors / business people, both from within the country and abroad.